Proceedings of the Workshop on QoE-based Analysis and Management of Data Communication Networks 2017
DOI: 10.1145/3098603.3098609
|View full text |Cite
|
Sign up to set email alerts
|

On Active Sampling of Controlled Experiments for QoE Modeling

Abstract: For internet applications, measuring, modeling and predicting the quality experienced by end users as a function of network conditions is challenging. A common approach for building application speci c Quality of Experience (QoE) models is to rely on controlled experimentation. For accurate QoE modeling, this approach can result in a large number of experiments to carry out because of the multiplicity of the network features, their large span (e.g., bandwidth, delay) and the time needed to setup the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Here a machine learning classification model is used to intelligently select network instances for experimentation. In a prior work [16], we have shown that active learning gives a significant gain over uniform sampling in QoS-QoE modeling. However, active sampling requires a single output QoE definition (classification label) to be predefined before the experimentation phase, making the resulting dataset biased towards the given classification model.…”
Section: The Experimental Setupmentioning
confidence: 97%
“…Here a machine learning classification model is used to intelligently select network instances for experimentation. In a prior work [16], we have shown that active learning gives a significant gain over uniform sampling in QoS-QoE modeling. However, active sampling requires a single output QoE definition (classification label) to be predefined before the experimentation phase, making the resulting dataset biased towards the given classification model.…”
Section: The Experimental Setupmentioning
confidence: 97%
“…Indeed, YouTube QoE is known to decrease fast with the join time and the duration of stalls. Explicit functions exist in the literature to capture this dependence, further details in [7]. We stream thousands of videos in variable network conditions, then for each streaming session, we measure the join time and the duration of stalls, which together give us an estimation of the QoE for this session on a scale from 1 to 5.…”
Section: B From Network Performance To Qoementioning
confidence: 99%
“…With this approach, we aim at making network measurements reused by different QoE models and allowing ACQUA to provide estimations of the QoE without running the applications themselves, hence reducing the overhead on the mobile. The way we build these models and their accuracy have been discussed in two of our recent papers for two popular applications, Skype [6] and YouTube [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have applied pool based uncertainty sampling in a previous work [9] where we presented a first validation with a trace collected and labeled with uniform sampling, thus forming our ground truth. With the help of a video streaming QoE case, we validated the gain of uncertainty sampling and its capacity to reduce the training cost by an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%